Crystal structure of deracoxib, C17H14F3N3O3S. Issue 1 (March 2023) - Kaduk, James A.; Gindhart, Amy M.; Gates-Rector, Stacy; Blanton, Thomas N.
Abstract : The crystal structure of deracoxib has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional theory techniques. Deracoxib crystallizes in space group Pbca (#61) with a = 9.68338(11), b = 9.50690(5), c = 38.2934(4) Å, V = 3525.25(3) Å 3, and Z = 8. The molecules stack in layers parallel to the ab -plane. N–H⋯O hydrogen bonds link the molecules along the b -axis, in chains with the graph set C1, 1(4), as well as more-complex patterns. N–H⋯N hydrogen bonds link the layers. The powder pattern has been submitted to ICDD for inclusion in the Powder Diffraction File™ (PDF®).